Seed Yield and Quality of Lowland Rice (Oryza sativa L.) as Influenced by Nitrogen from Organic and Chemical Sources - Khatun, Amina; Sultana, Hasina; Islam, A B M Jamiul; Bhuiya, Md Sultan Uddin; Saleque, Md Abu (The Agriculturists, 2016)
A field experiment was conducted at the Bangladesh Rice Research Institute (BRRI) experimental farm during boro season of 2010-11 to determine the effect of nitrogen from organic and chemical sources on rice seed yield and quality. Six treatments- (i) N-control, ii) Optimum dose of nitrogen (164 kg N ha-1) from urea, iii) 50% N from urea and 50% N from CD (cow dung), iv) 50% N from urea and 50% N from PM (poultry manure), v) 100% N from CD and vi) 100% N from PM were compared. The experiment was conducted in a randomized complete block design with four replications. Two boro varieties BRRI dhan28 and BRRI dhan29 were used as test crops. The urea + PM treatment gave similar seed yields to that of urea in both the varieties. The PM treatment gave similar seed yield to that of urea + PM in BRRI dhan28, but BRRI dhan29 gave significantly lower seed yield in PM than the urea + PM. Sole cowdung or poultry manure application produced significantly lower seed yield than urea + PM treatment and sole urea application. The application of N from cowdung and poultry manure had no effect on rice seed quality as compared to that obtained with urea. The Agriculturists 2015; 13(1) 109-118